Extração de sólidos solúveis da semente de romã (Punica granatum L.) utilizando solventes alternativos e misturas - Furtado, Maria Luiza Bianchetti (2022)
This evaluation work was carried out with the objective of editing pomegranate seeds and bioactives using different solvents. The first part was characterized by the characterization of the hypotheses of this study, determined results that were presented as presented in a form and presented phenolic components. With the use of solvents, solvent mixtures and solvent solvents (35ºC and 55ºC), for the purpose of the thermodynamic parameters of trading. Solvent obtained or higher yield obtained from solids obtained soxhlet. The thermodynamic alternatives of the data show how ΔH were positive for ethanol, acetone and ethyl acetate, and negative for isopropane; ΔS were positive for ethanol, acetone and ethyl acetate, and negative for isopropanol; and ΔG were negative for all extractions performed with all solvents, indicating that the processes are spontaneous, endothermic, using ethanol, acetone and ethyl acetate, and the process is exothermic when using isopropanol. A third part addressed the optimization of seed processing processes using mixtures with, and for this purpose a composite rotational design (DCCR) was carried out to study the effects of independent variables available for studies of classification and ethyl acetate in the mixture with the ethanol index and variable yield variables, the ethanol index in the responses, the phenolic acid content and the antioxidant activity by the ABTS method and DPPH EC50. The result showed that the addition of acetone and ethyl satin solvents and the increase in temperature did not have a significant 5% effect on the yield of extractions of soluble and non-phenolic solids. For antioxidants and acceptance rates, the addition of ethyl acetate and temperature significantly influence the receiving process. The optimum is in the range between 0 to 20% ethyl acetate, 25 to 50% acetone and higher temperatures. Through the results obtained, it can be demonstrated that the pomegranate seeds contain a significantly relevant content of addition studies, being the introduction of the use of alternative extractions and different solvents, in order to add value to this agro-industrial oil.